A Quantitative Model of Social Capital and Economic Development in Islamic Palm Oil Farming Communities - Nurlaili; M Nasor; Heni Noviarita; Rini Setiawati; Mohd Syahril Ahmad Razimi (CV. FOUNDAE, 2025)
Background: Economic development in farming communities is linked to social capital embedded in interactions, norms, and collective practices. In palm oil farming settings, social capital is often assumed to be uniformly beneficial, yet empirical patterns can differ across dimensions. Aims: This study examines the associations between social capital dimensions and economic development in palm oil farming communities using a quantitative model. Method: A cross sectional quantitative design was used with primary data from structured questionnaires administered to smallholder palm oil farmers in Central Lampung Regency, Indonesia. Social capital was operationalized into social networks, reciprocity, trust, social norms, and social values. Ordinary least squares multiple regression was applied. Results: The regression results show heterogeneous associations. Social norms have a positive and statistically significant association with economic development indicators. Trust has a statistically significant negative association. Social networks, reciprocity, and social values are positive but statistically insignificant. The negative association of trust may reflect unequal power relations, elite control in marketing arrangements, or internal stratification and distrust within farmer groups, conditions that can raise transaction frictions rather than strengthen collective outcomes. Conclusion: Social capital is not uniformly beneficial. Its association with economic development depends on specific dimensions and local institutional context, supporting the use of quantitative modeling to capture these differences.